Arabic Language Learning Strategies for ICP Students of Dirosat Islamiyah Al-Amien Prenduan Institute - Muhaimin, Anwar; Ramadhan, Yusfar (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2024)
This study aims to identify and analyze Arabic language learning strategies applied to students in the international class program (ICP) at the Al-Amien Prenduan Islamic University Institute. With the increasing need for Arabic language proficiency among international students, it is important to understand the most effective methods and approaches in this educational context. The research method used is a qualitative approach with data collection techniques through interviews, observations, and document studies. The results of the study indicate that Arabic language learning strategies in ICP involve a combination of communicative approaches, task-based learning, and the use of technology. This approach is designed to improve students' speaking, listening, reading, and writing skills by considering the cultural aspects and social context of the Arabic language. This study also found that the implementation of these strategies was successful in improving students' motivation and Arabic language skills, as well as providing recommendations for further improvements in the learning process. These findings are expected to contribute to the development of more effective Arabic language teaching methods in international class programs.